Determinants affecting culinary undergraduates’ future career decision in post-COVID era - Zaihan, Asma; Mohd Khamis, Nor Farawahidah; Ahmad Ruslin, Elyssa Maisara; Md Mubin, Siti Ida Isnainie; Fudzali, Fadzhiathul Azwa (Universiti Teknologi Mara Cawangan Pulau Pinang, 2023)
The COVID-19 virus represents a threat to the hotel sector, and future crises are still very much a possibility. This study aims to identify factors affecting culinary undergraduates’ future career in post-covid era among students to better understand how such a crisis affects the desirability of pursuing a career in the hospitality industry. This study used quantitative methodology based on the positivist paradigm. A self-administered questionnaire was used and distributed to 254 respondents in Universiti Technologi MARA Cawangan Pulau Pinang. The data gathered was analyzed using SPSS version 21. Pearson’s Correlation test was conducted on the research variables to measure the strength of the linear relationship between two variables. Results showed that all three hypotheses which are salary, self-efficacy, and personal interest significantly influence culinary future career choices among undergraduate students. The authors of this study anticipate that it can benefit aspiring talent in the culinary industry and aid in restoring the appeal of employment in the sector by providing significant leverage points that may be used to help reduce the confusion among undergraduates in choosing a career because of a crisis, like COVID-19. It is recommended that future research to encompass all public universities and their undergraduate student populations to further validate the findings of this study.